The policy of fiscal austerity and its impact on the public budget deficit in Egypt for the period (2004-2021) - Basit Mohammed *, Saja; Saleh Salman, Mohammed (Journal of Economics and Administrative Sciences, 2024)
The study aimed to take austerity measures to address the public budget deficit in Egypt, as the public budget deficit is one of the most important economic problems that affects the public financial situation, and the Egyptian economy does not differ from the rest of the world’s countries in terms of the increasing public budget deficit. The analytical approach was used to show the impact of the financial austerity policy on the  public Budget deficit. Egypt succeeded in adopting a policy of financial austerity, as after several years of slow growth and weak economic performance, the Egyptian economy began to recover. The financial situation improved as a result of the implementation of the value-added tax and reductions in energy subsidies, in addition to the floating of the pound, Which led to the improvement of the external sector and, thus, an increase in exports in exchange for a decrease in imports, in addition to the International Monetary Fund and many international evaluation institutions praising the results of the economic reform program, as these institutions modified their view of Egypt positively and praised the success of liberalizing the exchange rate, which confirms the increasing foreign investor confidence.  Paper type: Research paper